Online Shopping Protection in Indonesia: A Social & Legal Discourse - Rinjani, Andini Gita; Sabri, Ahmed Badaruddin Muhammad (Faculty of Law, Universitas Negeri Semarang, 2022)
In this modern era, Electronic Commerce or business transactions today's generation called it the online shopping loved everybody in terms of its use, because it is very effective and can efficiently time so that one can conduct transactions wherever and whenever. It turns out it is very bersiko. Internet is an open network that can trigger the occurrence of data manipulation factors which would harm the party. Finally, emerging form of software security solutions, which did not give full guarantee to be free from loss, it certainly can reduce public confidence. Based on the relevant legislation, namely Law No. 40 of 20014 any emerging risks and capable of causing the loss can be the object of insurance. This means that all forms of transactions in e-commerce should be insured in order to ensure certainty and security in the transaction. The rules regarding insurance with respect to electronic commerce should be regulated specifically in a chapter in the Law No. 40 of 2014 on insurance, so as to provide clear regulation about insurance sehubungannya with e-commerce. Through normative legal research methods are expected to be able to prove how a clear legal basis to the problem in question, especially in the perspective to businesses as well as the Insurance Act itself.